KETERAMPILAN SOSIAL YANG PEMBELAJARANNYA MENGGUNAKAN SNOWBALL THROWING, TALKING STICK DAN TARI BAMBU - Siti Ruhibah; Edy Purnomo; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2021)
This study aimed to determine whether there are differences between the social skills of students using cooperative learning Snowball Throwing, Talking Stick and Bamboo Dance. The method used in this a comparative study with the experimental approach. A population of 252 and a sample of 106 students by random cluster sampling technique. Retrieving data with documentation and observation. Hypothesis testing using the formula of one-way analysis of variance and t-Dunnet further test. RESULTS: (1) There are differences in the average social skills of students whose learning using Snowball Throwing, Talking Stick and Dance Bamboo (2) social skills of students whose learning using Snowball Throwing better than Talking Stick (3) average social skills of students whose learning using Snowball Throwing better than Bamboo Dance (4) average social skills of students whose learning using the Talking Stick better than Bamboo Dance.Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan keterampilan sosial antar siswa yang pembelajarannya menggunakan kooperatif tipe Snowball Throwing , Talking Stick dan Tari Bambu. Metode yang digunakan adalah penelitian komparatif dengan pendekatan eksperimen. Populasi berjumlah 252 dan sampel 106 siswa dengan teknik cluster random sampling. Pengambilan data dengan dokumentasi dan observasi. Pengujian hipotesis menggunakan rumus analisis varians satu arah dan uji lanjut t-Dunnet.Hasil penelitian : (1) Ada perbedaan rata-rata keterampilan sosial siswa yang pembelajarannya menggunakan Snowball Throwing, Talking Stick dan Tari Bambu (2) Keterampilan sosial siswa yang pembelajarannya menggunakan Snowball Throwing lebih baik dibandingkan Talking Stick (3) Rata-rata Keterampilan sosial siswa yang pembelajarannya menggunakan Snowball Throwing lebih baik dibandingkan Tari Bambu (4) Rata-rata keterampilan sosial siswa yang pembelajarannya menggunakan Talking Stick lebih baik dibandingkan Tari Bambu.Kata kunci: keterampilan sosial, model pembelajaran kooperatif snowball throwing, talking stick dan tari bambu.